The Effect Of Several Concentrations Of Growth Regulatory Substance (ZPT) Auxin NAA (Naphthalene Acetic Acid) On The Root Growth Of Vanila (Vanila planifolia Andrew) Cuttings - Raesita Dorhayne Timburas; Arthur G. Pinaria; Edy F. Lengkong (Sam Ratulangi University, 2023)
Vanilla cultivation is generally propagated vegetatively, namely by stem cuttings, but the growth potential is still very low, so special treatment is required, such as giving growth regulators (ZPT) which can stimulate growth. ZPT which is often found in the market is Auxin which functions to stimulate growth and stimulate cell division and enlargement. The use of auxin NAA growth regulator causes faster and longer root formation, forming a strong, compact and fibrous root system. This study was an experimental study using a completely randomized design (CRD) consisting of 7 treatments and 5 replications so that the number of plants was 35 plants. The observed variables measured were root growth time, root length, and root dry weight. The results of the research statistically showed that the ZPT NAA treatment had a significant effect on the root appearance and root length variables, but had no significant effect on the root length variable. Keywords: Vanilla, ZPT, Auxin NAA Abstrak Budidaya vanili umumnya diperbanyak secara vegetatif yaitu dengan stek batang, namun potensi tumbuhnya masih sangat rendah sehingga diperlukan perlakuan khusus seperti pemberian zat pengatur tumbuh (ZPT) yang dapat merangsang pertumbuhan. ZPT yang banyak dijumpai di pasaran adalah Auksin yang berfungsi untuk merangsang pertumbuhan dan merangsang pembelahan dan pembesaran sel. Penggunaan zat pengatur tumbuh auksin NAA menyebabkan pembentukan akar lebih cepat dan lama, membentuk sistem perakaran yang kuat, kompak dan berserat. Penelitian ini merupakan penelitian eksperimen dengan menggunakan metode Rancangan Acak Lengkap (RAL) yang terdiri dari 7 perlakuan dan 5 ulangan sehingga jumlah tanaman adalah 35 tanaman. Variabel pengamatan yang diukur adalah waktu tumbuh akar, panjang akar, dan berat kering akar. Hasil penelitian secara statistik menunjukkan bahwa perlakuan ZPT NAA berpengaruh nyata terhadap variabel kenampakan akar dan panjang akar, namun tidak berpengaruh nyata terhadap variabel panjang akar. Kata kunci: Vanili, ZPT, Auxin NAA